UJI AKTIVITAS ANTIBAKTERI AIR PERASAN JERUK LEMON (Citrus limon) DALAM MENGHAMBAT PERTUMBUHAN Staphylococcus aureus DI LABORATORIUM ANALIS KESEHATAN POLITEKNIK PIKSI GANESHA BANDUNG - Ria Khoirunnisa Apriyani; Widiantini (Jurnal Infokes, 2021)
This study aims to determine the antibacterial activity of lemon juice (Citrus limon) in inhibiting the growth of  Staphylococcus aureus, determine the  largest concentration of lemon juice (Citrus limon) which has inhibitory zones the greatest in inhibiting the growth of Staphylococcus aureus and knowing the Minimum Inhibitory Concentration (MIC) of lemon juice (Citrus limon) in inhibiting the growth of Staphylococcus aureus. The data in this study were collected by using experimental descriptive method and a Completely Randomized Design (CRD). This activity test through the Kirby-Bauer diffusion technique with a bacterial cell number of 10-6CFU/ml. The test were carried out using lemon juice with various concentrations of 25%, 50%, 75% and 100%, using negative controls with sterile distilled water, using positive controls with antibiotics gentamicin and carried out up to 3 repetitions. The result shows that lemon juice (Citrus limon) has antibacterial activity at all concentrations of 25%, 50%, 75% and 100% in inhibiting the growth of Staphylococcus aureus with a weak category of 1,5 mm – 4,17 mm. While the biggest concentration of lemon juice (Citrus limon) is ata a concentration of 100% with an average inhibition zone of 4,17 mm with a weak category. And the Minimum Inhibitory Concentration (MIC) of lemon juice (Citrus limon) is at a concentration of 19%.